Sistem Scoring Conversion TOEFL Studi Kasus Unit Pelaksana Teknis Bahasa Politeknik Negeri Cilacap - Cahya Vikasari; Soedihono Soedihono (Universitas Darussalam Gontor, 2017)
Language center of state Polytechnic of cilacap is an english language training institution, and one of them is TOEFL test. Academic data processing of Language Center still uses conventional ways. Some of them are registering and data processing of participants. The result of TOEFL test is still conducted using microsoft excel. The growth of education and technology is demanding the language center to make innovation in improving service and interaction that can be accepted well. The system will be developed by using based web and dekstop that function to quicken registering process, performance, and eficiency in administration data processing and scoring TOEFL in Language Center. By internet/intranet media, it will ease in registering process and data processing through dekstop without having a need many conventional activities.